Refleksyjność w kontekście podmiotowości i sprawczości nauczyciela. Wnioski dla kształcenia nauczycieli - Dróżka, Wanda (Rocznik Pedagogiczny, 2022)
The article’s aim is to describe and analyse reflectivity as a desirable dimension of the professionalism of a contemporary teacher and the space of his becoming and development. It’s described on basis of author’s own research works and analyses, in reference to the so-called “reflective cognitive approach” in the social sciences, presented by Giddens, Sztompka, Bourdieu and studies and analyses on the basis of pedeutology (Czerepaniak-Walczak, Kwiatkowska, Mizerek, Klus-Stańska, Gołębniak). In this text, in addition to referring to the aforementioned trends and concepts, the approach of Margaret S. Archer is introduced, in which the three components of subjectivity, reflexivity and agency are closely related and determine the essence of man as a person. In this way, author exposes the issue of the teacher as a person. This perspective, along with the social approach, in the current conditions (due to their technological complications and global tensions), is particularly desirable. Meanwhile, these are neglected issues in Polish education policy; the teacher’s (technical) competence model (limited professionalism) does not seem to be enough while facing constant changes in the socio-political arena and in the media. They affect the axiological condition of teachers, cause their identity confusion, uncertainty, low sense of subjectivity, lack of strong legitimacy and trust in society. The article also addresses the issue of education to reflectivity as the basic subjective competence of the teacher, the quality of his person, education as a task of modern education and the education and professional development of teachers.